Characterization and Optimization of Calcination Process Parameters for Extraction of Aluminum from Ethiopian Kaolinite. (10th March 2022) - Kassa, Adamu Esubalew; Shibeshi, Nurelegne Tefera; Tizazu, Belachew Zegale
Abstract : The present study aimed to optimize the calcination process parameters (viz., temperature, time, and particles size) for the extraction of aluminum from Ethiopian kaolinite. The kaolinite calcination was done in the temperature of 600–700°C, time of 120–180 min, and particles size of 106–355 μ m. The extraction of aluminum from calcined kaolinite was carried out at fixed acid concentration of 3 M, temperature of 80°C, liquid-to-solid ratio of 12 mL g −1, time of 120 min, and stirring speed of 700 rpm. The chemical composition of kaolinite was determined using XRF. Moreover, kaolinite, metakaolinite, and extracted aluminum were characterized by XRD, TGA, DSC, and FTIR. The XRF result of the kaolinite was mainly silicon oxide (55.76% w/w), aluminum oxide (32.02% w/w), and loss on ignition (11.17% w/w). Calcination of kaolinite produced amorphous metakaolinite due to the dehydroxylation reaction as shown by the FTIR results. Three endothermic peaks and one exothermic peak were detected in the thermal analysis of the kaolinite due to water removal, impurities decomposition, dehydroxylation reaction, and phase change from metakaolinite to spinel, respectively. The extracted aluminum proportionally increased with kaolinite calcination temperature and time. However, the extracted aluminum increased as the particles size reduced. The extracted aluminum was in the form of aluminum chloride hexahydrate and trigonal crystalline structure. The optimum values of the degree of conversion of kaolinite dehydroxylation reaction and extracted aluminum of 0.992 and 71.28% w/w were obtained at the optimum kaolinite calcination temperature of 700°C, time of 180 min, and particles size of 106 μ m, respectively.